Enhancing the leaching effect of an ion-absorbed rare earth ore by ameliorating the seepage effect with sodium dodecyl sulfate surfactant - Zhang, Yongbing; Zhang, Boyuan; Yang, Siqi; Zhong, Zhigang; Zhou, Hepeng; Luo, Xianping (International journal of mining science and technology, 2021)
Ameliorating the problem of low leaching efficiency, long leaching period, and high agent consumption should be studied to efficiently exploit ion-absorbed rare earth ore resources. In this study, the surfactant sodium dodecyl sulfate (SDS) is used to enhance the leaching effect of an ion-absorbed rare earth ore by ameliorating the seepage effect for the first time. The effects of surfactant concentration, leaching agent dosage, solution flow velocity, and solution pH on the leaching rate were explored, and the mechanism of SDS was discussed. Under the optimum conditions, the addition of a small amount of SDS (mass fraction 0.04%) can increase the leaching rate by about 5%, shorten the leaching period, and reduce the consumption of the leaching agent. SDS significantly ameliorates the seepage effect of the ore body by reducing the surface tension of the leaching agent and ameliorating the wettability of the mineral surface. This effect is the main factor that improves the leaching efficiency. DFT (density functional theory) calculation results show that SDS can react with rare earth ions, which reduces the adsorption strength on clay mineral surfaces. Hence, rare earth ions are easily exchanged by ammonium ions, and mass transfer is enhanced.